Mekanisme Pricing And Product Display Toko Klontong Pesantren Salaf : Studi Kasus Pondok Pesantren Panyeppen Pamekasan Madura - Kamali Kamali; Mansur Mansur; Fitria Nur Masithoh; Sukamto Sukamto; Aang Kunaifi (INAIFAS Press, 2020)
The pricing and display of products at the grocery store at the Panyeppen Pamekasan Islamic Boarding School are separate uniqueness. This descriptive study found new things that were happening in the salaf pesantren. Pricing is based on mutual benefits between buyers and sellers on the principle of deliberation between managers and the trade principle